The murder of King Tut [compact disc, unabridged] : the plot to kill the child king : a nonfiction thriller - Patterson, James, 1947- (Hachette Audio, 2009)
Novelist James Patterson teams up with non-fiction writer Martin Dugard to uncover the mystery shrouding the death of Tutankhamun, commonly known as King Tut. Ever since Tut's tomb was discovered in 1922, many scholars have speculated on the boy king's fate. Patterson and Dugard utilize modern technology, including X-rays and other forensic data, in an attempt to solve a 3,000-year-old mystery.